Umbilical granuloma in infants: treatment modalities between the past and present. - Muhamed Jassim, Fadhle; Ali Farooq , Al-Mayoof (European Journal of Pediatric Dermatology, 2026)
Umbilical granuloma is a common condition encountered during infancy. Several treatment modalities are available, but the optimal management strategy has not yet been clearly defined. This study aims to compare the effectiveness of five therapeutic approaches used for umbilical granuloma. A prospective cohort study was conducted at a tertiary pediatric surgery center over a 20-month period, including patients up to three months of age with umbilical granuloma. Patients were allocated into five groups according to the treatment modality chosen by their parents. They were followed for 10-45 days, and healing and failure rates were calculated for each therapeutic strategy. A total of 158 patients were included, with a mean age of 29 days. Males were predominant, with a male-to-female ratio of 1.46:1. Low birth weight, prematurity, and delayed cord separation showed low incidence rates (7.6%, 6.3%, and 5.7%, respectively). Healing rates were 100% for silver nitrate and surgical excision, 76.7% for topical steroids, 65.8% for table salt, and 44.1% for ethanol; the differences were statistically significant (P = 0.00001).